Gradual in vitro Evolution of Cefepime Resistance in an ST131 Escherichia coli Strain Expressing a Plasmid-Encoded CMY-2 β-Lactamase - Donà, Valentina; Scheidegger, Maximilian; Pires, João; Furrer, Hansjakob; Atkinson, Andrew; Babouee Flury, Baharak (Frontiers in Microbiology, 2019)
Background In a previous report, a clinical ST131 Escherichia coli isolate (Ec-1), producing a plasmid-encoded AmpC β-lactamase CMY-2, evolved in vivo under cefepime (FEP) treatment to the FEP-resistant Ec-2 strain expressing an extended-spectrum β-lactamase CMY-33. To compare factors responsible for in vitro and in vivo FEP resistance, we reproduced in vitro FEP resistance evolution in Ec-1. Methods FEP-resistant mutants were generated by subjecting Ec-1 (FEP MIC=0.125 mg/L) to sub-inhibitory concentrations of FEP. MICs were obtained by broth microdilution or Etest. Strains were sequenced on an Illumina HiSeq platform. Transcriptional levels and plasmid copy numbers were determined by real-time PCR. Outer membrane proteins (OMPs) were extracted and separated by SDS-PAGE. Growth kinetics was evaluated by measuring OD450. Results The CMY-2 expressed by Ec-1 evolved to a CMY-69 (strain EC-4) by an Ala294Pro substitution after 24 passages. After 30 passages, the FEP MIC increased to 256 mg/L (strain EC-32). SDS PAGE did not reveal any lack of OMPs in the mutant strains. However, blaCMY transcription levels were up to 14-times higher than in Ec-1, which was partially explained by mutations in the upstream region of repA resulting in a higher copy number of the blaCMY-harboring IncI1 plasmid. All mutants showed a slight growth defect but no significant difference in relative growth rates compared to Ec-1. Conclusion In vitro sub-inhibitory concentrations of FEP resulted in the selection of resistance mutations altering the H-10 helix of the CMY-2 and increasing the plasmid copy number. Appropriate dosing strategies may help preventing resistance evolution during treatments.